Tatanan Skema Neuron Dan Benak (Syaraf & Otak) Makhluk Hidup Dalam Al-Qur'an - Ahmad Farid; Laelatul Qodriyah; Romidah (CV. ALIM'SPUBLISHING, 2023)
The Qur'an is the holy book of Muslims which functions as a way of life and guidance for humans in living their lives in the world. The Qur'an contains many aspects and parts of life, including worship, muamalah, warnings and knowledge. -The Al-Qur'an is a revelation whose truth is absolute, so from a scientific point of view, both science and society must be in harmony with the information contained in the Al-Qur'an. Science, especially science, is related to events in the universe. Nature and humans are sources of knowledge which are often referred to as the macro world and the micro world. However, there are other sources of knowledge, especially those that come from revelation or the Koran. Not all verses of the Koran touch on natural issues, of the 6,236 verses there are only 800 verses. These verses became known as kauniyah verses. There are several patterns of explanation of the Qur'an in these kauniyah verses. One example of the Islamization of science is the Islamic insight into nerve cells in the brain. The interaction of cells, tissues, organs and organ systems in the human body cannot be separated from the existence of nerve cells. The human nervous system consists of the central nervous system and the peripheral nervous system. The central nervous system is divided into two parts, namely the brain and spinal cord. The brain as the central nervous system has a central role in regulating body functions. The Qur'an mentions brain neurons.